Implementasi E-Learning Berbasis Edukati Pada Mata Pelajaran ICT Untuk SMAS Dwi Putra Ciputat - isrofi, Muhammad; Ardiansyah, Ahmad Fikri; Efendi, Yasin; Palestina, Sari (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2025)
The learning process that takes place at SMAS Dwi Putra still uses conventional learning methods that only rely on printed books and learning is not yet interactive. This research aims to implement a new method for continuing learning using education-based e-learning. The aim of this research is to determine the validity and practicality of education-based e-learning. This research methodology is Research and Development (R&D) using the 4D development model, namely define, design, development and disseminate. The subjects of this research were 10 class X students and 1 SMAS Dwi Putra teacher in ICT subjects, especially Microsoft Word material. The research results showed that the Edukati e-learning media validity questionnaire was 84% in the very valid category, and the material validity questionnaire was 94% in the very valid category. Apart from that, the practicality results for the teacher response questionnaire were 96% in the very practical category, and the student response questionnaire was 8.36% in the very practical category. According to this data, it can be concluded that the implementation of Edukati-based e-learning in ICT subjects, especially Microsoft Word material at SMAS Dwi Putra, was declared very valid and very practical.